2016
DOI: 10.1186/s12861-016-0137-6
|View full text |Cite
|
Sign up to set email alerts
|

Lack of effects of ooplasm transfer on early development of interspecies somatic cell nuclear transfer bison embryos

Abstract: BackgroundSuccessful development of iSCNT (interspecies somatic cell nuclear transfer) embryos depends on complex interactions between ooplasmic and nuclear components, which can be compromised by genetic divergence. Transfer of ooplasm matching the genetic background of the somatic cell in iSCNT embryos is a valuable tool to study the degree of incompatibilities between nuclear and ooplasmic components. This study investigated the effects of ooplasm transfer (OT) on cattle (Bos taurus) and plains bison (Bison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…However, when mtDNA was added to porcine oocytes with sufficient mtDNA, there were no additional benefits 11 . Whilst it has been also reported that the transfer of donor ooplasm containing mtDNA was neither detrimental or beneficial to embryos up to the 8–16 cell stage 60 , donor mtDNA can modify the germline as it is detectable in the offspring’s oocytes 22 . Nevertheless, donor mtDNA appears to decrease in foetal tissues suggesting a skewed bias towards the germline 22 .…”
Section: Discussionmentioning
confidence: 99%
“…However, when mtDNA was added to porcine oocytes with sufficient mtDNA, there were no additional benefits 11 . Whilst it has been also reported that the transfer of donor ooplasm containing mtDNA was neither detrimental or beneficial to embryos up to the 8–16 cell stage 60 , donor mtDNA can modify the germline as it is detectable in the offspring’s oocytes 22 . Nevertheless, donor mtDNA appears to decrease in foetal tissues suggesting a skewed bias towards the germline 22 .…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the experimental studies (14 out of 24) were conducted in animals with good quality oocytes. The effects of mitochondrial transfer were evaluated by comparing IVF/ICSI (intracytoplasmic sperm injection) vs mitochondrial supplementation in combination with ICSI (mICSI) or by comparing somatic cell nuclear transfer (SCNT) in animals of the same species (Lee et al 2017, Srirattana & St John 2018, Xu et al 2019) or involving different species (iSCNT) (Sansinena et al 2011, Hua et al 2012, Takeda et al 2012, Gonzalez-Grajales et al 2016, with or without mitochondrial transfer. Mitochondrial transfer was also compared in the context of parthenogenetic development in bovine species (Takeda et al 2005).…”
Section: Context (Objectives Of Studies)mentioning
confidence: 99%
“…After the transfer of the nucleus into the enucleated oocyte, the cytoplast–karyoplast complex is subjected to an electric pulse that not only induces the fusion of the somatic cell nucleus with the enucleated oocyte to form a new complex, but also promotes the release of intracellular calcium that initiates cellular activation (Pereira & Freitas, 2009). In general, the successful development of a reconstructed embryo depends on the complex interactions between the cytoplast and the nuclear structure during embryonic development; failures in this interaction can cause problems during early cleavage and embryonic development (González-Grajales et al , 2016).…”
Section: Overview Of the Iscnt Technique And Its Limitationsmentioning
confidence: 99%
“…iSCNT preserves and even expands genetic variability when somatic cells of different individuals representative of the original biodiversity of a population are collected for its use (Loi et al , 2001). In addition, interest in cloning has increased not only for the conservation of endangered species, but also for the multiplication of reproducers with better genetic characteristics (Saini et al , 2015), basic research on cell epigenetic status (Saragusty et al , 2016), embryonic development (González-Grajales et al , 2016), and the production of induced pluripotent cells (Sukparangsi et al , 2018).…”
Section: Introductionmentioning
confidence: 99%